Sociocultural correlates and epidemiological patterns of non-alcoholic beer consumption: a cross-sectional study in Poland - Andrzej Silczuk; Aleksandra Lewandowska; Tomasz Baran; Tytus Koweszko; Paulina Mularczyk-Tomczewska; Julia Gujska; Magdalena Tatara; Małgorzata Gałecka (BMJ Open)
Objectives To investigate the sociocultural and epidemiological factors associated with non-alcoholic beer (NAB) consumption in Poland, including motivations for use, consumption context, and its reported impact on alcohol consumption patterns.Design Cross-sectional survey study.Setting Community setting across Poland; data were collected in December 2024.Participants A total of 1114 adults aged 18–84 years (mean age: 47.1±14.4 years; 54.3% female) completed the questionnaire. Participants were recruited through an online panel using stratified quota sampling to approximate national population distributions by age, sex and region. Inclusion criteria were age ≥18 years and residence in Poland. No exclusion criteria beyond informed consent were applied.Interventions Not applicable.Primary and secondary outcome measures The primary outcome was current NAB use, defined as self-reported consumption of NAB. Secondary outcomes included sociodemographic correlates, reasons for use, consumption contexts and self-reported changes in alcoholic beer consumption following NAB adoption.Results 70.6% of respondents reported current NAB use. Multivariable logistic regression showed that age 18–49 years (p<0.05), being married or in an informal relationship (OR=1.71; 95% CI: 1.19 to 2.45; p=0.004), residing in a household with ≥3 members (OR=1.61; 95% CI: 1.03 to 2.52; p=0.04) and being employed or self-employed (OR=1.65; 95% CI: 1.18 to 2.31; p=0.003) were independently associated with NAB use. Among NAB users (N=787), primary motivations included the ability to drive (28.2%), hydration (16.9%) and enjoying the taste without alcohol (12.1%). Regarding alcohol consumption, 31.6% reported using NAB to reduce their intake of alcoholic beer, and 22.6% stated that they had fully replaced alcoholic beer with NAB. Conversely, 37.0% reported no change in their alcohol consumption, 5.8% switched back to alcoholic beer only and 2.9% reported increased alcohol use after initiating NAB.Conclusions NAB consumption in Poland is associated with identifiable sociodemographic characteristics and motivated by practical and health-related considerations. While nearly half of current users report reduced or substituted alcohol intake, a substantial proportion incorporate NAB into existing drinking routines without change or with increased alcohol use. These findings suggest a heterogeneous behavioural impact, underlining the need for nuanced public health messaging and further research into the long-term effects of NAB use on alcohol-related outcomes.